2016
DOI: 10.1093/rpd/ncw009
|View full text |Cite
|
Sign up to set email alerts
|

Soil Gas Radon Measurement Around Fault Lines on the Western Section of the North Anatolian Fault Zone in Turkey

Abstract: Soil gas radon activity measurements were made around the western section of the North Anatolian Fault Zone. In the study, the variation of radon concentration at 12 different locations along the fault line was monitored by using LR-115 (solid-state nuclear track detectors) detectors for 12-monthly periods. Twelve radon stations were determined in the study region, and in each station, LR-115 films were installed in the borehole of ∼50 cm. The recorded radon concentration varies from 29 to 7059 Bqm-3 with an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 46 publications
0
4
0
1
Order By: Relevance
“…They ob served av er age 222 Rn con cen trations of 3630, 4411 and 4717 Bq m -3 , and the 220 Rn con cen trations of 13, 65, and 84 Bq m -3 at sam pling depths of 50, 100 and 150 cm, re spec tively. Sim i lar low val ues in the range of 29 to 7059 Bq m -3 at 50 cm depth were re ported for soil ra don measure ments around fault lines in the west ern part of the north Ana to lian fault zone (Tur key) by Yakut et al (2017).…”
Section: Resultsmentioning
confidence: 99%
“…They ob served av er age 222 Rn con cen trations of 3630, 4411 and 4717 Bq m -3 , and the 220 Rn con cen trations of 13, 65, and 84 Bq m -3 at sam pling depths of 50, 100 and 150 cm, re spec tively. Sim i lar low val ues in the range of 29 to 7059 Bq m -3 at 50 cm depth were re ported for soil ra don measure ments around fault lines in the west ern part of the north Ana to lian fault zone (Tur key) by Yakut et al (2017).…”
Section: Resultsmentioning
confidence: 99%
“…The detectors were calibrated with a radium standard in the Turkish Atomic Energy Authority Çekmece Nuclear Research and Training Centre (TAEK‐CNAEM) and the calibration factor was found to be 0.054 Bqdm −3 track −1 cm 2 . 42 The correct radon activity concentration depends on a well-calibrated detector. Therefore, in the present study, the calibration factor was determined for the same geometry conditions as the studied samples.…”
Section: Methodsmentioning
confidence: 99%
“…Bedrocks, superficial deposits, and faults (fracturing) also affect radon flux. Faults increase radon flux, and the influence of superficial deposits depends on the physicochemical characteristics of the deposits [82,122,123]. The condition of the soil surface also significantly influences radon flux.…”
Section: Diffusion-advectionmentioning
confidence: 99%